Analisis Peran Human Capital dalam Meningkatkan Kesempatan Kerja di Provinsi Jawa Barat: Studi Kontekstual di Kabupaten Tasikmalaya - Sadiah, Ati; Hakim, Lukman; Sabandi, Muhammad; Indah Sari, Pratiwi (Universitas Batanghari Jambi, 2025)
Employment issues in West Java Province, particularly in Tasikmalaya Regency, represent a complex and strategic challenge. High open unemployment rates, skill mismatches, and the misalignment between workforce competencies and industrial demands are persistent problems. In this context, human capital—which encompasses education, training, skills, and health—is considered a key factor in expanding employment opportunities. This study aims to analyze the role of human capital in increasing employment opportunities, focusing on Tasikmalaya Regency. A descriptive qualitative approach is employed, as outlined by Campbell and Pederson (2001), emphasizing a contextual and systematic understanding of institutional and social dynamics. Data were collected through in-depth interviews with vocational and university graduates, both job seekers and those currently employed, along with direct observation of job training activities in both urban and rural areas. Document analysis was also conducted to support the findings. The results indicate that strengthening human capital through relevant formal education, contextual job training, and equitable access to education and health services significantly contributes to improving employment prospects. Interregional disparities remain a major obstacle, necessitating affirmative policies based on data and local needs. Multi-stakeholder collaboration—among government, educational institutions, industry, and communities—is essential to establish a more inclusive and sustainable employment system.